2020
DOI: 10.1007/978-981-10-0753-8_24-1
|View full text |Cite
|
Sign up to set email alerts
|

Parents with Psychiatric Conditions

Abstract: Parental psychiatric disorders, which are not uncommon, affect various aspects of family functions and child development. The heightened risk for development of psychopathology in offspring is associated with the effects of inherited genetic susceptibility and environmental influences. Parental psychopathology could limit their ability of synchrony, responsivity, and affect expression so that it is difficult for them to provide an optimal support for their offspring's emotional and physiological development. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The risk of psychopathology in children may increase by reasons of hereditary-genetic susceptibility and environmental factors. Studies have shown that people with psychiatric disorders experience different levels of parenting difficulties, depending on the characteristics of the disorder and the presence/absence of environmental support (Yamane et al, 2020;Erdim et al, 2015) The vast majority of developmental scientists and clinicians agree that child-rearing, parenting, and more general family functions are naturally transferred from generation to generation. This process is especially important in understanding parenting behavior because daily interactions between parent and child are critical in forming the attachment in an early life period.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of psychopathology in children may increase by reasons of hereditary-genetic susceptibility and environmental factors. Studies have shown that people with psychiatric disorders experience different levels of parenting difficulties, depending on the characteristics of the disorder and the presence/absence of environmental support (Yamane et al, 2020;Erdim et al, 2015) The vast majority of developmental scientists and clinicians agree that child-rearing, parenting, and more general family functions are naturally transferred from generation to generation. This process is especially important in understanding parenting behavior because daily interactions between parent and child are critical in forming the attachment in an early life period.…”
Section: Introductionmentioning
confidence: 99%